Drivers of Intentions Toward Integrated Islamic Commercial and Social Finance: Evidence from Indonesian Muslim Millennials - Safira, Zahra; Priantina, Anita; Nurhanani Aflizan Mohamad Rusli (Journal of Islamic Economics (JoIE), 2025)
Introduction: Islamic financial concept enables an integration between commercial and social finance. It has a substantial benefit for the economy. This study aims to investigate the factors that influence Muslim millenials intention to contribute toward integrated Islamic commercial and social finance (IICSF), especially in Indonesia case. Research Methods: Using modified TPB framework, primary data is collected from respondents located in Jakarta, Bogor, Depok, Tangerang, and Bekasi. Partial Least Square-Structured Equation Modelling (PLS-SEM) is utilized to analyze the data. Results: The result indicates that knowledge, religiosity, attitude, subjective norms, and perceived behavioral control have significant impact on Muslim millennials’ intention to contribute toward IICSF. Meanwhile, relative advantage is found to be insignificant. Conclusion: To boost the practice and implementation of IICSF, it is important to raise public knowledge, religiosity, attitude, and to increase education so society are well educated about the products. This study contributes to the limited research on integrated Islamic finance from a consumer perspective, particularly focusing on the behavioral intentions of Muslim millennials in Indonesia.